The Creditor's Role as the Fiduciary Guarantee Recipient in Movable Property Rights Protection System - Rauf, Nur'Ainun Sri A.; Abdussamad, Zamroni; Fazri Elfikri, Nurul; Fathurrohman, Aulia (Estudiante Law Journal, 2025)
The execution process of fiduciary guarantees in bankruptcy cases in Indonesia faces significant legal challenges. Although Law No. 42 of 1999 on Fiduciary Guarantees grants priority rights to creditors holding fiduciary guarantees, its implementation is often hindered by unclear procedures and inconsistencies between fiduciary guarantee law and bankruptcy law. This study aims to analyze the obstacles creditors face in executing fiduciary guarantees in bankruptcy cases and to find legal solutions to enhance legal certainty for creditors. The research method uses a normative approach, analyzing relevant regulations and court rulings, and comparing fiduciary guarantee law with bankruptcy law. The results indicate that legal uncertainty, a 90-day execution suspension after bankruptcy, and the role of the receiver, which delays the execution of fiduciary guarantees, are the main barriers. Therefore, it is recommended to implement legal reforms that provide clearer and more efficient execution procedures and ensure better protection of creditors' rights in bankruptcy situations. Thus, this study contributes to improving the fiduciary guarantee legal system in Indonesia.